Polypoidal choroidal vasculopathy with spontaneous regression of subfoveal changes – case report - Lachowicz, Ewelina; Kubasik-Kładna, Katarzyna; Mozolewska-Piotrowska, Katarzyna; Karczewicz, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Purpose: To report a patient with polypoidal choroidal vasculopathy (PCV) with spontaneous regression of subfoveal changes during follow-up. Material and methods: The seventy six years old men was referred to the treatment of exudative type of age related macular degeneration (AMD) in the RE. The routine ophthalmological examination, the optical coherence tomography (OCT), fluorescein angiography (FA), and indocyanine green angiography (ICGA) were performed. Results: Decreasing of visual acuity of the RE and abnormal result of the Amsler test, hemorrhagic and exudative changes near inferior-temporalis vascular arcade were observed. Intraretinal fluid in the OCT was noted. FA revealed parapapillaris changes suggesting CNV. ICGA showed the presence of branching vascular network extending from choroidal vasculature (BVN) and polypoidal and aneurysmal vascular terminal lesion (PL) localized under retinal pigment epithelium (RPE). Conclusions: Based on the results PCV was diagnosed and the patient was referred to laserotherapy. Due to the regression of the eye fundus changes during the period of observation, confirmed by control OCT and FA the treatment was not implemented.